KNOWLEDGE AND AWARENESS OF CHILD ABUSE AND NEGLECT AMONG DENTISTS - A SURVEY - T. K, Hariprasath; K. , R. Don; R, Gayatridevi (International Journal of Psychosocial Rehabilitation, 2020)
Child abuse is a state of emotional, physical, economic, and sexual maltreatment met out to be a person below the age of 18 and is a globally prevalent phenomenon. However, in India, there has been no understanding of the extent, magnitude, and trends of the problem. In view of the high proportion of oral and facial injuries seen in victims of child abuse, dentists are in a strategic position to recognize and report suspected cases. A cross-sectional survey was undertaken to assess the knowledge and attitude of dentists regarding child abuse and neglect and to identify the barriers to child abuse and neglect. A questionnaire of 21 questions was created and entered in the online survey creator ‘Google Forms’ and shared among the population of 100 dentists individually and privately, and the data collected were subjected to statistical analysis using SPSS software. Statistical tests used were descriptive statistics and chi square tests. A P value less than 0.05 was considered statistically significant. Confidence level was set at 90%. Overall responses to the questions were 95%. A significant difference between MDS and BDS dentists in knowledge and awareness of child abuse and neglect was noted, with the BDS graduated dentists showing more knowledge and awareness. Results of this study suggest that dentists need an effective education and awareness campaign to increase their knowledge and awareness of all aspects of CAN.